Discrimination of Korean Native Chicken Lines Using Fifteen Selected Microsatellite Markers - D. W. Seo; M. R. Hoque; N. R. Choi; H. Sultana; H. B. Park; K. N. Heo; B. S. Kang; H. T. Lim; S. H. Lee; C. Jo; J. H. Lee (Asian-Australasian Journal of Animal Sciences, 2013)
In order to evaluate the genetic diversity and discrimination among five Korean native chicken lines, a total of 86 individuals were genotyped using 150 microsatellite (MS) markers, and 15 highly polymorphic MS markers were selected. Based on the highest value of the number of alleles, the expected heterozygosity (He) and polymorphic information content (PIC) for the selected markers ranged from 6 to 12, 0.466 to 0.852, 0.709 to 0.882 and 0.648 to 0.865, respectively. Using these markers, the calculated genetic distance (Fst), the heterozygote deficit among chicken lines (Fit) and the heterozygote deficit within chicken line (Fis) values ranged from 0.0309 to 0.2473, 0.0013 to 0.4513 and −0.1002 to 0.271, respectively. The expected probability of identity values in random individuals (PI), random half-sib (PIhalf-sibs) and random sibs (PIsibs) were estimated at 7.98×10−29, 2.88×10−20 and 1.25×10−08, respectively, indicating that these markers can be used for traceability systems in Korean native chickens. The unrooted phylogenetic neighbor-joining (NJ) tree was constructed using 15 MS markers that clearly differentiated among the five native chicken lines. Also, the structure was estimated by the individual clustering with the K value of 5. The selected 15 MS markers were found to be useful for the conservation, breeding plan, and traceability system in Korean native chickens.